The Influence Of "Serumpun" Between Malaysia And Indonesia In The Post Cold War Era - Kanmani, A/P Rengasamy (Universiti Malaysia Sarawak (UNIMAS), 2015)
This paper systematically analyses about the nature of Malaysia and Indonesia relationship under the concept of Serumpun during the post- Cold War era. It being with discussion on bilateral relations before and after both nations gained independence. Besides that, various factors have discussed in this paper about the history of Malays in Malaysia and Indonesia relationship. Other than that, discussion about the meaning of concept serumpun in depth within two state relationships and critically analyses about the role of concept serumpun after independence and role of leader to strengthen the relationship rather then bring rivalry in the relations. Last but not least, this study has identified some gaps between two nations starting from after they gained independence from the colonial powers. Therefore, the concept serumpun is still not relevant in the context of bilateral relation in two states under foreign policy because two states are more focus on national interest rather than relationship due to the influence of globalization.